Use of an educational intervention with audiovisual material to improve knowledge and practices on metaxenic diseases in schoolchildren. Peru - Muñoz del Carpio-Toia, Agueda (2019)
Objective. Identify the level of knowledge and practices on metaxenic diseases in school children before and after an educational intervention with audiovisual material. Methods. Pre post design study developed in three public schools in Arequipa, Peru. Knowledge and practice surveys were applied before and after the educational intervention based on audiovisual material focused on the Aedes Aegypti vector and the role of schoolchildren in the identification and prevention of the disease. Results Surveys were applied to 300 schoolchildren between six and fifteen years. The level of knowledge and practices improved significantly in all students after the educational intervention, both in the aspects of knowledge (global, agent, symptoms, prevention and complications) with those of practices (individual and family). Conclusions It was shown that educational innovation based on multimedia audiovisual products improves knowledge about the Aedes aegypti vector and practices for preventing transmission of metaxenic diseases in schoolchildren.